2023
DOI: 10.3390/ijms242316901
|View full text |Cite
|
Sign up to set email alerts
|

Opaganib (ABC294640) Induces Immunogenic Tumor Cell Death and Enhances Checkpoint Antibody Therapy

Lynn W. Maines,
Staci N. Keller,
Charles D. Smith

Abstract: Antibody-based cancer drugs that target the checkpoint proteins CTLA-4, PD-1 and PD-L1 provide marked improvement in some patients with deadly diseases such as lung cancer and melanoma. However, most patients are either unresponsive or relapse following an initial response, underscoring the need for further improvement in immunotherapy. Certain drugs induce immunogenic cell death (ICD) in tumor cells in which the dying cells promote immunologic responses in the host that may enhance the in vivo activity of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…To summarize, our proteomics and lipidomic study in fibroblasts from ARSACS patients highlighted altered levels of ceramides and DGs, which may potentially be involved in impaired cell signaling in ARSACS etiopathogenesis. Confirmation of these findings in motor neurons would allow us to speculate on targets for treatments ( Maines et al, 2023 ) or monitor disease severity through surrogates of metabolic status in ARSACS.…”
Section: Discussionmentioning
confidence: 75%
“…To summarize, our proteomics and lipidomic study in fibroblasts from ARSACS patients highlighted altered levels of ceramides and DGs, which may potentially be involved in impaired cell signaling in ARSACS etiopathogenesis. Confirmation of these findings in motor neurons would allow us to speculate on targets for treatments ( Maines et al, 2023 ) or monitor disease severity through surrogates of metabolic status in ARSACS.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, we evaluated the antitumor activity of opaganib in combination with irinotecan (IRIN) plus temozolomide (TMZ) because IRIN + TMZ is the backbone for treatment of recurrent or refractory NB alone or in combination with additional potential therapies [110,111]. C57BL/6 mice bearing LLC tumors were selected for the initial exploratory study because of their established tumor growth rates and responsiveness to opaganib [45]. This study demonstrated a significantly increased efficacy of opaganib + IRIN + TMZ relative to vehicle-and IRIN +TMZ-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited success in NB therapy, targeting checkpoint proteins continues to be explored in clinical trials of this disease [27]. We have previously demonstrated that opaganib promotes immunogenic cell death (ICD) in tumor cells, including Neuro-2a cells [45], which can enhance therapeutic responses to checkpoint antibodies. Additionally, both c-Myc [112] and N-Myc [113] have been shown to modulate anti-tumor immune suppression, and so a combination of Myc inhibitors with cancer immunotherapy may improve NB patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations